A home for autistic child: residential spaces intervention in Malaysia - Tukiman, Izawati; Abdul Rahim, Asiah; Mohd Yaacob, Naziaty; Abd Samad, Nur Amirah (Faculty of Design and Architecture, Universiti Putra Malaysia, 2015)
In Conventions on the Right for Children (CRC) 1995, Malaysia has highlighted the rights of children whom will be monitored from the aspects of survival, protection, development, and participation. This research will be focusing on one of the survival an aspect which is living spaces or accommodation for children with Autism Spectrum Disorder (ASD). The increasing number of children with Autism Spectrum Disorder (ASD) has alerted many on their education, health and safety, because these children are prone to injuries. Therefore it is very important to provide these children with homes that are educationally interactive, healthy and safe. Many studies emphasized on the importance of the learning environment for autistic children, but none have focused on the idea of inclusive and universal design in houses. This research will employ both qualitative and quantitative research methods based on environmental and behavioural studies. Additionally, this paper will discuss literature reviews from various aspects that are associated with this research. The aim of the study is to establish a relationship between the physical environment and the architectural factors that affect issues of daily living in order to recognize autism-friendly inclusive house designs. This research is beneficial for both children with autism and able-bodied children.